Ceramides play a significant role in the response of Pogostemon cablin to bacterial wilt by regulating the ABA pathway - Jian Li; Dan-Xia Wu; He-Nan Bao; Ke-Yu Li; Ming-Yong Zhang; Yun-Hao Sun; Kuai-Fei Xia (BMC Plant Biology)
Abstract As a strategic resource for both medicine and essential oil, the healthy development of the Pogostemon cablin industry is crucial for the traditional medicine and fragrance sectors. Bacterial wilt represents one of the most significant threats to patchouli cultivation; however, the molecular mechanisms underlying P. cablin’s response to bacterial wilt remain unexplored. Here, we conducted transcriptome and metabolome analyses, revealing an increase in the expression of genes associated with lipid pathways and a corresponding rise in the concentration of lipid metabolites in P. cablin following infection by the bacterial wilt pathogen SY1. Further lipidomics analysis demonstrated a significant upregulation of ceramide levels due to SY1 infection. Additionally, hormone analysis indicated that SY1 significantly induced an increase in abscisic acid (ABA) concentration, accompanied by the upregulation of genes involved in the ABA synthesis pathway and its downstream signaling pathways. Furthermore, we treated P. cablin seedlings with the ceramide synthase inhibitor FB1, which significantly reduced ceramide concentration in P. cablin. FB1 treatment also inhibited the expression of ABA-synthesizing genes, leading to a notable decrease in ABA concentration and downstream pathway genes. These data indicate that ceramides and ABA may participate in P. cablin’s response to SY1.